Menilik Persoalan Kisas dan Poligami dalam Konteks Fikih Keadilan - Shuhufi, Nadyatul Hikmah (Jurusan Hukum Acara Peradilan dan Kekeluargaan, 2023)
The correct application of Islamic law will provide security, peace and tranquility. Like kisas law and polygamy law include the values and principles of justice both conceptually and practically. The legal provisions must be understood correctly because they allow contextualization to occur which refers to the context of the times that are constantly changing. Then, this article is analyzed using the context of fiqh of justice. This resulting in the conclusion that kisas punishment can save lives, property, and human rights in general. While the polygamy law on the one hand is a solution to justice for family life in an emergency. Keyword: Keywords: Kisas, Polygamy, Fiqh of Justice